Human development and economic growth in Malaysia / Hazzatul Nadia Ismail - Ismail, Hazzatul Nadia (2017)
Human capital or human development is normally observed as one of the contributing factors of economic growth. Economic growth mentioned being a permanent objective of economic policy in the world, whether in the medium or long run as it is the development process. Human development plays an important role in growth to the extent of better economic performance in the country. Numerous findings mentioned human development contribute positive and significant relationship towards economic growth. On the other hand, some papers mentioned negative relationship and statistical insignificance. Thus, these relationship often been argued as it has been mentioned over time that human development does contribute towards national economic growth. This research paper was carried out to observe the significant relationship or connection between human development and economic growth. The main objectives of this paper are to identify what elements of human development and how those elements contributing to economic growth in Malaysia. As the economic growth will be the dependent variable; education, health, and human development index are the independent variables. An ordinary least square method — regression model will be conducted to test the relation in a case of Malaysian data. It is hope that this research paper can contribute to the improvement of human development and economic growth. Keywords: Human Capital, Human Development, Growth